Translation, Globalization and Translocation The Classroom and Beyond (Palgrave Studies in Translating and Interpreting, 2018)
This book examines the spaces where translation and globalization intersect, whether they be classrooms, communities, or cultural texts. It foregrounds the connections between cultural analysis, literary critique, pedagogy and practice, uniting the disparate fields that operate within translation studies. In doing so, it offers fresh perspectives that will encourage the reader to reappraise translation studies as a field, reaffirming the directions that the subject has taken over the last twenty years. Offering a comprehensive analysis of the links between translation and globalization, this ambitious edited collection will appeal to students and scholars who work in any area of translation studies.